Socioeconomic status is not associated with the delivery of care in people with diabetes but does modify HbA1c levels: An observational cohort study (Elzha‐cohort 1). Issue 5 (24th January 2021) - van Bruggen, Sytske; Kasteleyn, Marise J.; Bonten, Tobias N.; Chavannes, Niels H.; Numans, Mattijs E.; Rauh, Simone P.
Abstract: Background: Structured primary diabetes care within a collectively supported setting is associated with better monitoring of biomedical and lifestyle‐related target indicators amongst people with type 2 diabetes and with better HbA1c levels. Whether socioeconomic status affects the delivery of care in terms of monitoring and its association with HbA1c levels within this approach, is unclear. This study aims to understand whether, within a structured care approach, (1) socioeconomic categories differ concerning diabetes monitoring as recommended; (2) socioeconomic status modifies the association between monitoring as recommended and HbA1c. Methods: Observational real‐life cohort study with primary care registry data from general practitioners within diverse socioeconomic areas, who are supported with the implementation of structured diabetes care. People with type 2 diabetes mellitus were offered quarterly diabetes consultations. "Monitoring as recommended" by professional guidelines implied minimally one annual registration of HbA1c, systolic blood pressure, LDL, BMI, smoking behaviour and physical activity. Regarding socioeconomic status, deprived, advantageous urban and advantageous suburban categories were compared to the intermediate category concerning (a) recommended monitoring; (b) association between recommended monitoring and HbA1c. Results: Aim 1 (n = 13 601 people): Compared to the intermediate socioeconomic category, no significant differences in odds of being monitored as recommended were found in the deprived (OR 0.45 (95% CI 0.19‐1.08)), advantageous urban (OR 1.27 (95% CI 0.46‐3.54)) and advantageous suburban (OR 2.32 (95% CI 0.88‐6.08)) categories. Aim 2 (n = 11 164 people): People with recommended monitoring had significantly lower HbA1c levels than incompletely monitored people (−2.4 (95% CI −2.9; −1.8) mmol/mol). SES modified monitoring‐related HbA1c differences, which were significantly higher in the deprived (−3.3 (95% CI −4.3; −2.4) mmol/mol) than the intermediate category (−1.3 (95% CI −2.2; −0.4) mmol/mol). Conclusions: Within a structured diabetes care setting, socioeconomic status is not associated with recommended monitoring. Socioeconomic differences in the association between recommended monitoring and HbA1c levels advocate further exploration of practice and patient‐related factors contributing to appropriate monitoring and for care adjustment to population needs.